2010
DOI: 10.1063/1.3489889
|View full text |Cite
|
Sign up to set email alerts
|

Chaogates: Morphing logic gates that exploit dynamical patterns

Abstract: Chaotic systems can yield a wide variety of patterns. Here we use this feature to generate all possible fundamental logic gate functions. This forms the basis of the design of a dynamical computing device, a chaogate, that can be rapidly morphed to become any desired logic gate. Here we review the basic concepts underlying this and present an extension of the formalism to include asymmetric logic functions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
26
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(27 citation statements)
references
References 31 publications
0
26
0
Order By: Relevance
“…This morphing logic functionality enabled by nonlinear dynamics is reminiscent of what has been termed 'chaogates' [11], and in that language we have indeed shown that simple and highly scalable integrate-and-fire circuits can implement chaogates. However, our system also goes beyond the abilities so far proposed for chaogates.…”
Section: B Gdpsi To Implement and Morph Between Any Possible Operationmentioning
confidence: 95%
“…This morphing logic functionality enabled by nonlinear dynamics is reminiscent of what has been termed 'chaogates' [11], and in that language we have indeed shown that simple and highly scalable integrate-and-fire circuits can implement chaogates. However, our system also goes beyond the abilities so far proposed for chaogates.…”
Section: B Gdpsi To Implement and Morph Between Any Possible Operationmentioning
confidence: 95%
“…In 2002 Munakata, Sinha and Ditto described basic principles of implementing the most fundamental computing functions by chaotic elements [2]. The use of one-dimensional schemes like tent map and logistic map are possible to create different logic functions [2,3].In 2010 Ditto, Miliotis, Murali, Sinha and Spano used this feature that chaotic systems can yield a wide variety of patterns to produce main logic operators [4]. Low and one-dimensional chaotic systems can express a stunning variety of different behaviors as a function of time, of their initial conditions or of their parameters [5].…”
Section: Introductionmentioning
confidence: 97%
“…This was the initial theoretical step indicating the possibility to build logic devices with dynamic architecture for computers and by 2005 Kuo [5] briefly reviewed the potential of chaotic elements to perform universal computing. More recently, Ditto and collaborators [4] reviewed the basic tenets of the chaos computing emerging paradigm and also discussed some proof of concept chips. In many theoretical works, the logistic maps are the chaotic elements used to simulate logic gates.…”
Section: Introductionmentioning
confidence: 99%